Determinants for milk fever An epidemiological study of Swedish dairy cows - Daresjö, Sofia (2020)
Milk fever is a worldwide disease, seen mainly in dairy cows. At the onset of lactation the cow is not prepared for the sudden calcium requirement, which causes a drop in the blood calcium and the cow develops hypocalcaemia. Calcium is needed for the correct function of both nerves and muscles in the body. A cow suffering from milk fever can show a variety of clinical signs, such as being recumbent, having a reduced appetite and having cold extremities. In the worst cases of milk fever the cow can develop a comatose state and die. To cope with the loss of calcium the cow has several mechanisms in the body involving the kidneys, intestines and bones. These include increased absorption of calcium from the kidneys and intestines and a resorption of calcium from the bones.